The historical observation of the relationship between foreign trade and employment: Evidence from China’s manufacturing industry - Yan, Sen; Yu, Jiamin (Edelweiss Applied Science and Technology, 2025)
This paper aims to explore the relationship between foreign trade and employment in China's manufacturing sector, covering data analysis from 1998 to 2014. We used various econometric methods to analyze the impact of different components of foreign trade on related manufacturing employment. The findings indicate that export trade has a significant positive effect on employment in China's manufacturing sector, while import trade generally exerts a suppressive impact on employment, particularly imports from countries other than the United States. Specifically, the influence of imports from the United States is positive but not significant, warranting cautious interpretation. Additionally, the study elucidates the mechanisms of influence, suggesting that foreign trade affects employment levels in relevant industries through its impact on aggregate supply and demand. Furthermore, this study provides policy recommendations, including promoting trade development and optimizing trade structure, actively engaging in trade negotiations to address trade frictions, and focusing on domestic circulation to stabilize employment. These measures offer valuable references for policymakers to ensure the robust development and employment growth of China's manufacturing sector amid a complex and changing international environment.